Neo-Latin Love Elegy in the Croatian Humanism: Tradition and Innovation - Novaković, Darko (2000)
Neo-Latin love elegies are often seen as series of more or less attractive documents on the Nachleben of certain Roman elegiac poets. Yet these efforts are not unimaginative imitations of great classical examples: they are literary achievements in their own right which adapt the genre tradition of the Roman love elegy to different social and literary circumstances.
Projekt MZOS
ENG